Post-quantum blind signature protocol on non-commutative algebras - N.H, Minh; D.N, et al., Moldovyan; N.A, Moldovyan; A.A, Kostina; L.Q, Minh; L.H, Huong; N.L, Giang (Journal of Computer Science and Cybernetics, 2021)
A method for constructing a blind signature scheme based on a hidden discrete logarithm problem defined in finite non-commutative associative algebras is proposed. Blind signature protocols are constructed using four-dimensional and six-dimensional algebras defined over a ground finite field GF(p) and containing a global two-sided unit as an algebraic support. The basic properties of the used algebra, which determine the choice of protocol parameters, are described.